Brief Notes Towards a Collective Hong Kong Story: Place, Language, History and Politics - Lai-Ming, Hong Kong Baptist University, Tammy Ho (Asiatic: IIUM Journal of English Language and Literature, 2014)
For the last seven years, the online journal Cha: An Asian Literary Journal has been publishing poetic works investigating Hong Kong identity and politics. As such, Cha provides a useful source for exploring the different thematic concerns which have preoccupied post-handover writing on the city. In this short essay, I focus on four of these thematic areas (place, language, colonial history and politics) and discuss how they reflect changing political, economic and social realities within Hong Kong.